1982
DOI: 10.1093/jn/112.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Effects on Metabolism of Yucatan Miniature Swine Selected for Low and High Glucose Utilization

Abstract: Yucatan miniature swine have been selected for increased (high K) or decreased (low K) ability to utilize glucose based on an intravenous glucose tolerance test (IVGTT). In this study we tested the effect of obesity in conjunction with ad libitum, high sucrose or high starch diets on IVGTT and the insulin response to glucose in these two lines of animals. Either diet caused increased glucose utilization and an increased insulin response in the low K animals. Neither diet caused a change in these parameters in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Females from this strain rapidly became obese, and some developed insulin resistance and diabetes and exhibited both hyperinsulinemia and hyperglycemia during gestation and lactation. When these pigs were fed a high-fat diet and sucrose as the carbohydrate source, they had a marked increase in peripheral insulin concentration and prolonged elevation of plasma glucose (Phillips et al 1981). In this study, impaired glucose tolerance or dietary changes did not affect serum lipids except for an elevation in fasting free fatty acid concentration.…”
Section: Yucatan Minipigsmentioning
confidence: 56%
“…Females from this strain rapidly became obese, and some developed insulin resistance and diabetes and exhibited both hyperinsulinemia and hyperglycemia during gestation and lactation. When these pigs were fed a high-fat diet and sucrose as the carbohydrate source, they had a marked increase in peripheral insulin concentration and prolonged elevation of plasma glucose (Phillips et al 1981). In this study, impaired glucose tolerance or dietary changes did not affect serum lipids except for an elevation in fasting free fatty acid concentration.…”
Section: Yucatan Minipigsmentioning
confidence: 56%
“…Cohen as well as Laube et al (6,14) have suggested that high levels of sucrose in the diet (at least 50%) are required before diabetogenic effects occur in rats. Earlier work from this laboratory (24) has shown that re placing starch with up to 33.7% sucrose in the diet does not significantly alter glucose tolerance in Yucatan pigs. The alteration of fiber and fat content are thereby implicated as more significant factors influencing the changes that occurred.…”
Section: Resultsmentioning
confidence: 79%
“…Scientists have successfully genetically bred the Yucatan minipig for differential responsiveness to IVGTT 30 . In the 1970s, researchers at Colorado State University used selective breeding to develop two strains of Yucatan minipig with differing glucose tolerance: a 'low K' strain with a low glucose clearance rate and a 'high K' strain with a high glucose clearance rate.…”
Section: Discussionmentioning
confidence: 99%
“…The research team succeeded at selectively breeding these minipigs by targeting differential carbohydrate metabolism using practical techniques. Because of issues with inbred animals of large sizes, however, the researchers were able to breed only five generations of the low K strain of minipigs and four generations of the high K strain of minipigs 30 . By the seventh generation, the phenotype of low glucose tolerance in the low K strain seemed to disappear 32 .…”
Section: Discussionmentioning
confidence: 99%